The Uses And Gratifications Of Facebook.Com: An Exploratory Study Of University Students In Pakistan - Mahmood, Zubair (2019)
Facebook has a high penetration rate among university students in the Pakistan, yet few academic studies seek to theoretically understand its popularity and uses. This study explored university students' uses and gratifications of Facebook.com. The Uses and Gratifications Theory (U&G) approach is applied in this research because it has been tested by previous researchers, that with the U&G principle, users can gratify their needs through the very process of using a medium (Cutler & Danowski, 1980). The concept of an active audience, as active receivers with purposive media uses, is the core tenet of the adaptation of theory U&G perspective, and augments its application to the study of Facebook. The focus of study was to explore: (1) the patterns of using Facebook among university students in Pakistan (2) the needs of university students as gratified by using Facebook in Pakistan (3) the benefits of using Facebook among university students in Pakistan and (4) the motivations which induce students to use Facebook. This study utilized the U&G approach as introduced by Katz, Blumler, & Gurevitch, (1974) to understand the appeal of mass media to the audience, as well as the assumptions that are particularly applicable to interactive media. The Qualitative approach was used for this study and for the focus group discussion technique for data collection. A constant comparative technique method was applied for the analysis of data collected from 8 focus group discussions from the top three research based universities in Pakistan: University of Punjab, Lahore, Quaid-i-Azam University, Islamabad, and Agricultural University of Faisalabad.